Odpowiedzi

2009-10-24T18:09:54+02:00
A ) 2 (2√3 -√5)=4√3-2√5
b ) -√3(1+2√3)=2√3-6
c ) (√5+1)²=5+2√5+1=2√5+6
d ) (5√2-1)²=50-10√2+1=10√2+51
e ) (2√2 - 1)²=8-4√2+1=-4√2+9
f ) (2+√5)(1-√3)=2-2√3+√5-√15
2009-10-24T21:32:21+02:00
A ) 2 (2√3 -√5)=2 (√4×√3-√5) =2√12 - 2√5 = √4×√12 - √4×√5 = √48 - √20 = √48 - √20 = √22


b ) -√3(1+2√3)= (-1)√2 (1 + √4×√3 ) = √1×√2 ( 1+√12 ) = √2 ( 1√12 ) = √2 × √2√12 = √4× √12 = √48

c ) (√5+1)²= √25 + 1 = 5 + 1 = 6

d ) (5√2-1)²= 25 √4 - 1 = 25 × 2 - 1 = 50 -1 = 49

e ) (2√2 - 1)²= 4√4 - 1 = 4×4 - 1 = 16 - 1 =15

f ) (2+√5)(1-√3)= (√4 + √5)(√1 - √3) = √9 × √-2 = √-18